Vale moves to exit coal business - Argus Media (2021)
In its first step to exit the coal business, Brazilian mining firm Vale will acquire all stakes held by Japanese trading house Mitsui in the Moatize coal mine and Nacala corridor coal infrastructure in Mozambique.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

Mozambique: Following the rise of Islamist group al-Shabab in Cabo Delgado - Marie Toulemonde (The Africa Report.com, 2021)
A visual explanation of how Mozambique’s islamist group al-Shabab has grown over the years in the northern Cabo Delgado province.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict / conflito; extractive industries / indústrias extractivas

As Militants Seize Mozambique Gas Hub, a Dash for Safety Turns Deadly - Goldbaum, Christina; Schmitt, Eric; Walsh, Declan (The New York Times, 2021)
An agonizing choice for nearly 200 people holed up in a hotel as gunmen roamed unchecked: Wait overnight for rescue? Or make a run for it?
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; private sector / setor privado

Mozambique: Firing in Palma near Total's LNG project, population fleeing - Lusa (Mozambique, 2021)
The town of Palma, in Cabo Delgado, was under gunfire on Wednesday afternoon and the population is fleeing, different sources who were in communication with the headquarters of the district that hosts the gas projects in northern Mozambique told Lusa. Machine gunfire was heard in the town and the
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; private sector / setor privado

Multinational enterprises, political institutions, and violence: a case study from Mozambique - Mairoce, Carlos; Silberberger, Magdalene; Zweynert, Joachim (Journal of Institutional Economics, 2021)
Based on the concept of limited and open access orders (LAO/OAO), this paper explains what appears to be a paradox: how was it possible that a former civil war country, Mozambique, which had been extremely successful in attracting foreign direct investment (FDI) and which the International Monetary Fund praised as a great Sub-Sahara African success story in 2007, only a few years later found itself on the brink of a new civil war? We argue that the destabilization of the country was the result of a toxic mix of domestic politics and a massive inflow of FDI. FDI provided rents to an increasingly dominant state party, FRELIMO, which could be appropriated one-sidedly. It then used these rents to oppress RENAMO, its previous civil war enemy and currently its main opposition party, to monopolize power. This strategy seemed to be successful until RENAMO, faced with the risk of being politically marginalized (and of losing its rents accordingly), returned to armed conflict in 2013. By analyzing the links between the macro-level of national politics and the micro-level of an enterprise and by embedding the interplay between polity and economy into an international context, the paper also makes a theoretical contribution to the LAO/OAO concept.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - english / inglês; conflict - civil war / conflito - guerra civil; extractive industries / indústrias extractivas; private sector / setor privado

Mozambique: How Total plans to protects its $15bn major gas project - Le Bec, Christophe (The Africa Report.com, 2021)
Total is going ahead with its Mozambique LNG project despite a major armed insurgency in Cabo Delgado. This article discusses plans to secure its Afungi facility, including security forces involved. Facility employment is projected to triple by 2022, from 5,000 in 2020 to 15,000 by 2022.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; employment / emprego; extractive industries / indústrias extractivas; private sector / setor privado

Moma Titanium Minerals Mine, Mozambique - Mining Technology | Mining News and Views Updated Daily - Mining Technology (Mining-technology, 2021)
Moma, one of the world’s biggest titanium mineral deposits, is located 160km from the city of Nampula in Mozambique, Africa. It is owned and operated by Kenmare Resources. The mine contains the titanium minerals ilmenite, rutile and zircon, which are used as feedstock to produce titanium dioxide pigment. It started production of heavy mineral concentrate (HMC) containing these three minerals in April 2007. It produced 1,201,100t of HMC and shipped approximately 853,100t of finished products in 2020. Kenmare carried out an expansion at the mine ten years ago to fulfil the growing demand for titanium dioxide feedstock in the market. The expansion was aimed to increase the design capacity of the mine by 50% while increasing the mine’s reserve estimate and annual production of HMC. Construction work on the expansion began in December 2010 and the works were completed in December 2013. The expanded mine has a mine life of more than 100 years. The first shipment of concentrated mineral sands was dispatched from Mama in Q2 2019, following the commissioning of the product stream in Q4 2018. The Moma mine had more than 1,420 employees at the end of 2019.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; extractive industries / indústrias extractivas; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Relatório Independente da Iniciativa de Transparência na Indústria Extractiva - EITI (Extractive Industries Transparency Initiative (EITI), 2020)
Este é o nono relatório de reconciliação dos pagamentos efectuados pelas empresas que operam na indústria extractiva e os recebimentos do Estado. Foram reconciliadas 97% das receitas tributárias provenientes da indústria extractiva. As diferenças apuradas entre os pagamentos das empresas e os recebimentos do Estado correspondem a 0,17% dos montantes confirmados pelo Estado em 2019.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

The presource curse in Africa: Economic and political effects of anticipating natural resource revenues - Frynas, Jedrzej George; Buur, Lars (The Extractive Industries and Society, 2020)
The notion of the ‘resource curse’ suggests that large inflows of extractive industry revenues cause many adverse macro-economic and political effects. The resource curse literature focuses on the impact of actual inflows of extractive resource revenues. However, anticipation of future resource revenues can also lead to negative macro-economic and political effects even before resource extraction takes place, which points to the role of behavioral aspects of the ‘resource curse’. Using empirical evidence from three African countries, this article investigates to what extent the anticipation of future extractive revenues led to ‘presource curse’ effects. It finds that all three countries experienced negative effects as a result of anticipation of future extractive revenues, including economic growth volatility, higher levels of national debt, eroded governance and societal conflicts. Given the phenomenal increase in oil, gas and metal ore exploration across Africa, it is likely that many countries experience the negative effects of a presource curse without natural resource extraction or long before natural resources are actually extracted.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

The politics of domestic gas: The Sasol natural gas deals in Mozambique - Salimo, Padil; Buur, Lars; Macuane, Jose Jaime (The Extractive Industries and Society, 2020)
This article explores the ways in which the ruling Frelimo elite in Mozambique engaged creatively with the opportunities and constraints created by Sasol's Pande and Temane natural gas project as they have evolved from the early 2000s until today. This is a period that has seen ruling-elite actors become involved in various projects related to the production of electricity from ‘domestic natural gas’. We argue that focusing on the initial gas investment and how it evolved over time makes it possible to understand the dynamics related to deal-making during the formative years when the Mozambican petroleum industry was reformed by separating its commercial and regulatory functions. More specifically we explore how access to revenues and rents related to natural gas projects have evolved. We point out that, although the Pande-Temane gas project has increased revenue generation, most of the gas was sold to the South African major, Sasol, for a very low amount of revenue during the first phase of the project. Revenues from the second phase, starting in 2012, did not increase dramatically, even though Mozambique acquired access to 50% of the gas from the extension of the pipeline and increased production. Instead, the increase in domestic gas allocated to the Mozambican market involved the allocation and distribution of gas to private companies at special prices, most of which were controlled by dominant ruling-elite factions under the Chissano and Guebuza governments. We argue that this has been the main mechanism for the transfer of rents from the public to the private domain.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais

Extractive Industry Transparency Index 2019-2020 - Mapisse, Inocência; Mate, Rui; Cortez, Edson (Centro de Integridade Pública (CIP) / Public Integrity Centre, 2020)
The extractive industry, particularly the oil and gas sector, has proved promising in the Mozambican economy with potential to contribute to economic growth. It is expected that in the next 3 years the country will show growth in the order of two digits. However, in order to ensure the transmission of growth to economic development based on the exploitation of these resources, there are aspects that should not be ignored such as transparency in governance in the sector. This aspect is also recognized by the government of Mozambique through the Report on Transparency, Governance and Corruption published in July 2019, which emphasizes that the opacity in this sector can give rise to serious conflicts of interest and harm the perception of the population about the real benefits that this industry provides to the country. Although the country is part of the Extractive Industry Transparency Initiative (EITI), whose focus is on the reconciliation of payments made by companies and receipts reported by the Government in the extractive industry sector, there is a gap regarding detailed information on several aspects: tax, social, governmental and other equally relevant and that should be made available on a project-by-project basis.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais; transparency / transparência

Mozambique LNG Project Could Be Transformational For Mozambique — If Western Environmentalists Don’t Interfere | Africa Oil & Power (2020)
NJ Ayuk discusses the Mozambique LNG project.
Keywords: #Reporting & Media / Reportagem & Mídia; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; extractive industries / indústrias extractivas; private sector / setor privado

Como Está Cabo Delgado? Webinar 2: Economia Política Dos Recursos Naturais - Observatório do Meio Rural (2020)
Com a entrada no novo milénio, e em virtude do aumento da procura de matérias primas nos mercados internacionais, intensifica-se um modelo de desenvolvimento assente na exploração de recursos naturais. Em Cabo Delgado emerge uma economia extractiva, fortemente dirigida para mercados externos e dependente da oscilação de preços nos mercados internacionais, que o país não tem condições de controlar. Grandes multinacionais envolvem-se numa acesa competição pelo acesso a recursos, em complexas alianças com elites nacionais, também elas em disputa entre si. Neste webinar pretende-se reflectir sobre as lógicas de acumulação aqui envolvidas, assim como o impacto que poderá ter para Moçambique em termos de receitas fiscais, e de desenvolvimento nacional.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; M - political economy analysis (PEA) / análise de economia política (AEP); extractive industries / indústrias extractivas; natural resources / recursos naturais

Broadening the Analysis of Peace in Mozambique: Exploring Emerging Violence in Times of Transnational Extractivism in Cabo Delgado - Alberdi, Jokin; Barroso, Manuel (Global Society, 2020)
This article explores the contemporary expressions of violence and oppression linked to the action of the extractive industry in the northern province of Cabo Delgado, Mozambique. Twenty-five years after the signing of the General Peace Agreement, the debate on peace in the country has remained confined to the resurgence of armed clashes between RENAMO combatants and State security forces in recent years. It is proposed here, however, that the current range of violence that challenge peace in Mozambique is broader and more diverse, requiring an analysis that considers the arrival of transnational extractivism. This study, taking Cabo Delgado province as a case-study, aims to broaden the scope of academic debates by establishing a dialogue with the practice of local peacebuilding, and contributions from the critical political economy of development and the collective capability approach.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - civil war / conflito - guerra civil; conflict / conflito; extractive industries / indústrias extractivas

The Genesis of Insurgency in Northern Mozambique - Matsinhe, David M.; Valoi, Estacio (Institute for Security Studies (ISS), 2019)
Insurgents have attacked towns and villages in Cabo Delgado, the poorest province in Mozambique. The government has responded by sending in the military to stamp out the assailants, using ‘whatever it takes’, amid suspicions that foreign fighters from Tanzania have radicalised local youth who are behind the violence. Other measures to counter the violence include an extra-judicial state of emergency and the suppression of information.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; youth / juventude

Sound of One Hand Clapping: Information Disclosure for Social and Political Action for Accountability in Extractive Governance in Mozambique - Awortwi, Nicholas; Nuvunga, Adriano (IDS, 2019)
Corruption through opaque public contracts costs Africa billions of dollars in revenue loss annually. Globally, initiatives to address this have centred on information disclosure (ID) but under what conditions does it work to promote accountability in the extractive sector that for a long time has seen its revenue management as being a major cause of conflict in Africa? Our study on this issue in Mozambique reveals intriguing findings, which suggest that protagonists of ID would need to recalibrate their strategies for promoting accountability. The study on ID in extractive governance in Mozambique has found 17 factors that connect to result in citizen and institutional inaction in demanding government accountability. The lessons from the study for policy and practice are that unless there is a link between ID and a government’s reputation, which scales up to the risk of a ruling government losing power, accountability is unlikely to occur when new information is disclosed.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; corruption / corrupção; decentralization / descentralização; extractive industries / indústrias extractivas; natural resources / recursos naturais

Independent Report of the Extractive Industries Transparency Initiative - EITI (Extractive Industries Transparency Initiative (EITI), 2019)
This is the ninth report reconciling payments made by companies operating in the extractive industry and receipts from the State. 97% of tax revenues from the extractive industry were reconciled. The differences between the payments by the companies and the receipts from the State correspond to 0,17% of the amounts confirmed by the State in 2019
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

Moçambique - recessão antes do boom: Reflexões sobre picos de investimento e novas fontes de gás - Roe, Alan (2018)
Este artigo surge na sequência de um artigo anterior onde se considerou em termos gerais muitas das questões que Moçambique enfrenta hoje em dia na gestão dos seus novos recursos extractivos. Em primeiro lugar descreve-se o pico de investimento já desencadeado pelas novas descobertas de gás em Moçambique. Depois apresenta-se em resumo alguma da literatura mais recente sobre os efeitos desses picos noutros países e contextos. De seguida analisam-se os principais aspectos dos resultados económicos decepcionantes testemunhados até 2018, e analisase selectivamente algumas das implicações destes resultados nas políticas futuras. O artigo conclui explorando a epidemiologia de um grande pico do investimento público — uma questão que tem relevância para o pico adicional que ainda é esperado. Ao seguir esta sequência de argumento, procura-se igualmente compreender melhor diversas questões fundamentais de política geral que surgem no contexto das grandes descobertas de novos recursos.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - portuguese / português; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais

Mozambique - bust before boom: Reflections on investment surges and new gas - Roe, Alan R. (WIDER Working Paper Series, 2018)
This paper is a sequel to an earlier paper that looked in broad terms at many of the issues that Mozambique faces today in managing its new extractive resources. The paper first describes the investment surge that has already been prompted by new gas discoveries in Mozambique. It then summarizes some of the more recent literature that has examined the effects of such surges in other country contexts. It next examines the main aspects of the disappointing economic outcomes that have so far been seen through 2018, and selectively analyses some of the implications of these outcomes for future policy. The paper concludes by exploring the epidemiology of a large public investment surge—an issue that has relevance for the further surge that is still anticipated. In following this sequence of argument, the paper also throws light on a number of critical general policy questions that arise in the context of major new resource discovery.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; ⛔ No DOI found

Making Information Disclosure in Extractive Governance Count for Accountability in Mozambique - Awortwi, Nicholas; Nuvunga, Adriano (Partnership for African Social and Governance Research (PASGR), 2018)
A recent study on information disclosure in the extractive sector has found 18 factors that result in citizen and institutional (state and non-state) inaction in demanding government accountability. Conducted by the Partnership for African Social and Governance Research (PASGR) in collaboration with the Centre for Public Integrity (CIP), as part of the Action for Empowerment and Accountability (A4EA) research programme, the study shows that citizens and/or institutions are unlikely to demand government accountability when: • citizens’ are experiencing high levels of economic vulnerability but much of the access to economic opportunities are anchored around state patronage and network; • a single political party has dominated governments for a long period of time and the mode of selection of Parliamentarians is defined by a ‘party list’, and not directly elected by the people; • CSOs have weak citizens’ mobilisation strategies and information disclosure is presented in a written form in a context where adult illiteracy rate is 45%; • there is an institutional culture of ‘submissiveness’ created out of fear of the political regime
Keywords: G - Mozambique / Moçambique; L - english / inglês; accountability / responsabilização; extractive industries / indústrias extractivas

What are the prospects for Mozambique to diversify its economy on the back of 'local content'? - Dietsche, Evelyn; Esteves, Ana Maria (WIDER Working Paper Series, 2018)
In recent years, Mozambique has made international headlines for the significant hydrocarbon deposits found offshore. These have increased the country's extractive resource endowments, in addition to its mining and onshore natural gas sector. It is expected that these industries will contribute to economic diversification and social development, not least by means of procuring locally produced goods and services and hiring Mozambicans. A key factor to achieve this is building domestic capital?in people, institutions, and infrastructure.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; extractive industries / indústrias extractivas; natural resources / recursos naturais; private sector - CSR (corporate social responsibility) / setor privado - RSC (responsabilidade social corporativa); ⛔ No DOI found

Islamic Insurgency in Cabo Delgado: Extractive Industry, Youth Revolt and Global Terrorism in Northern Mozambique - Bonate, Liazzat J. K. (The University of the West Indies, St Augustine, 2018)
The violent insurgency in northern Mozambican province of Cabo Delgado, that started in October 2017 and is still ongoing, caught the government of the country and the public by surprise. Although this insurgency remains largely unexplored and little understood, the only study done so far has suggested that it is being carried out by Muslim youth connected to Islamic radicalism, in particular to the Harakat alShabaab of Somalia and its offshoots in Kenya, Tanzania, and as far as DRC.1 Islam has a long history in Mozambique, since probably the eighth century.2 According to the 2017 National Population Census, Muslims account for about 18% of the total population the country and 58% of the Cabo Delgado inhabitants. However, Mozambique had never had any visible Islamist radical political movement before.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; youth / juventude

Minas a céu aberto de Moçambique - Munguambe, Arcénio Artur; Mandlate, Clarência Matias (Wutivi University, 2018)
Moçambique é um dos países da África com muitos recursos naturais. O grau de conhecime nto geológico até agora atingido, mostra que todos os recursos minerais considerados apresentam perspectivas favoráveis para a sua exploração. A indústria extrativa é o sector que tem grandes empregadores de mão-de-obra e tem um grande impacto rural podendo constituir grandes focos de desenvolvimento e de combate a pobreza nas áreas onde se encontra inserido. Neste caso, o presente trabalho visa identificar os principais recursos naturais e agrupar em metálicos e não metálicos e as respectivas empresas mineradoras.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; extractive industries / indústrias extractivas; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Power, conflict and natural resources: The Mozambican crisis revisited - Macuane, José Jaime; Buur, Lars; Monjane, Celso Marcos (African Affairs, 2018)
This article explores how the present socio-economic crisis in Mozambique is linked to the prospects of natural resource windfalls for the country. Drawing on the political settlement approach, it explores how the distribution of power both within and outside the ruling elite is structured and consequently how the underlying political processes have been shaped by the expectations of natural resource windfalls. The article argues that the present socio-economic crisis in Mozambique is not due to national resource assets in themselves. Instead, the political and economic downturn in Mozambique should be understood as a manifestation of how the political settlement has been organized and rent mobilization controlled by the ruling elite. To understand how the prospect of rents from natural resource sectors have influenced the political settlement, we have argued that one has to look at the dynamics of power both within and outside the ruling elite and the incentives they create for elites to use the control of power and access to economic benefits to achieve narrow and short-term gains rather than inclusive and longer-term goals.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; conflict / conflito; extractive industries / indústrias extractivas; natural resources / recursos naturais; power / poder

The Project for Supporting the Promotion of Nacala Corridor Development - Final Report - Japan International Cooperation Agency (JICA) (Japan International Cooperation Agency (JICA), 2018)
Final JICA report on Nacala Corridor Development Project, whose objectives include: to clarify organizations for promoting and coordinating the implementation of development strategies for the Nacala Corridor Region in accordance with PEDEC-Nacala and to prepare for the implementation of high priority projects in accordance with PEDEC-Nacala. The study project commenced in April 2012 and the final study report was produced in April 2015.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - Nacala; G - central / centro; G - north / norte; GD - Lichinga; GP - Cabo Delgado; GP - Nampula; GP - Niassa; GP - Tete; GP - Zambézia; L - english / inglês; development partners / parceiros de cooperação; extractive industries / indústrias extractivas; infrastructure / infrastrutura; natural resources / recursos naturais; private sector / setor privado

Extractives and economic diversification in Mozambique: will local content do the trick? (Research Brief 2/2018, 2018)
Research Findings - It is unlikely that the extractives sector can any time soon be used to finance visionary transformation strategies aimed at achieving economic diversification. Due to the country’s fiscal situation and delays in developing the offshore natural gas sector, it seems that extractives will not provide additional revenues for at least another decade, if not longer. If the fiscal crisis results in the further deterioration of the provision of public goods and services, the business environment will become worse for the country’s micro, small and medium-sized enterprises. There is the risk that the gap will widen even further between the skills and entrepreneurial capabilities available in the country, and those required by foreign investment projects and their supply chains. Such a prospect does not match well with the expectations that local content policies can provide the silver bullet for diversifying the economy.
Keywords: FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - english / inglês; extractive industries / indústrias extractivas; natural resources / recursos naturais; private sector / setor privado

Inclusive Land Governance in Mozambique: Good Law, Bad Politics? - Cabral, Lídia; Norfolk, Simon (IDS Working Papers, 2016)
This paper analyses inclusive land governance in Mozambique. It focuses on the country’s legal framework and the DUAT, the right to use and benefit from the land. The DUAT is a distinctive element of the Mozambican legislation that has land as the property of the state but recognises land use rights for occupants and users on the basis of a unitary system of tenure. The challenges of putting in practice what is thought to be one of Africa’s most progressive legal frameworks are discussed. These are set against a context where despite land abundance there are concerns over land grabbing and dispossession of rural communities, which constitute over 70 per cent of the country’s population. The law may be progressive but government politics are not, as an increasingly hegemonic elite controls Mozambique’s political system and resources. In the Mozambican context, we addressed these themes and questions at two levels: the national level that concerns legal frameworks, institutional players, policies and processes, complemented by a focus on land governance practices at the local level. We selected the province of Nampula, in Northern Mozambique, as the focus of our analysis of local practices. The main reason for this choice was the strategic location of the province within the Nacala corridor, an area extending along the transport corridor connecting the Mozambican hinterland to the seaport at Nacala. The Nacala corridor is a region of rapid economic expansion that has been stimulated by the development of the transport network that comprises the railway connecting Nacala to the coal mine explored by Vale in Tete province, one of the largest foreign investments in Mozambique. Unsurprisingly, there has been considerable pressure over land for agriculture, forestry, mining as well as transport infrastructures and the corridor has become a hot spot for some of the most high-profile cases of land conflict in Mozambique (UNAC and GRAIN 2015). Nampula is also one of SDC’s target provinces.
Keywords: *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GP - Nampula; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); Northern PEA; agriculture / agricultura; extractive industries / indústrias extractivas; governance / governação; land governance / gestão de terra; law / direito; ⛔ No DOI found

Overblown expectations of the mining sector - Economist Intelligence (Economist Intelligence, 2016)
The government of Mozambique remains confident that its mining boom is set to accelerate in the coming years, despite weak sentiment in the global mining industry. Rising coal production and an eventual rebound in global prices will spur some growth in Mozambique's mining sector in 2016‑20 but we expect that, weighed down by infrastructure deficits and non-competitive policies, it will remain a relatively small contributor to GDP growth. Mozambique has untapped coal reserves estimated to be in excess of 20bn tonnes, as well as commercial quantities of aluminium, gold, titanium, graphite and gemstones. Plus, it benefits from a long coastline and geographic proximity to mineral-hungry markets in Asia. At the peak of the commodity super-cycle, investor interest in Mozambican mining soared; the contribution of the mining sector to GDP increased from 1.6% in 2009 to 3.2% in 2013, while government earnings from the sector swelled from US$40m in 2009 to over US$1bn in 2014.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

PEDEC-NACALA Final Study Report Analysis Report: Strategic Master Plan on Strengthening of Nacala Corridor Region-Wide Freight Network for Agricultural and Mining Sectors - Oriental Consultants Global Co., Ltd.; RECS International Inc.; International Development Center of Japan Kokusai Kogyo Co., Ltd. (Japan International Cooperation Agency (JICA), 2015)
This document was prepared as an analysis report for sharing a study result on a particular theme as part of ‘The Project for Nacala Corridor Economic Development Strategies (PEDEC-Nacala)’ which is a technical assistance project supported by Japan International Cooperation Agency (JICA) for the Government of Mozambique. PEDEC-Nacala formulated integrated development strategies for corridor development by an integrated approach involving several sectors and also by giving consideration to environmental and social aspects. The actual strategies formulated in PEDEC-Nacala and details of the present situation of the Nacala Corridor Region are compiled into the PEDEC-Nacala Final Study Report
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; agriculture / agricultura; development partners / parceiros de cooperação; extractive industries / indústrias extractivas; infrastructure / infrastrutura

Gás para desenvolvimento ou apenas dinheiro? - Hanlon, Joseph; Nuvunga, Adriano (Centro de Integridade Pública (Public Integrity Centre), 2015)
O gás de Moçambique pode ser usado para promover industrialização e desenvolvimento rural desde que, a partir de agora, sejam feitas as opções correctas. As actuais prioridades vão para os megaprojectos baseados na exportação, que prometem altos rendimentos mas que, tal como os megaprojectos anteriores, fazem pouco pela criação de empregos ou pela redução da pobreza. Os megaprojectos custando dezenas de bilhões de dólares são essenciais, mas o Conselho de Ministros pode orientar as negociações de maneira a darem a prioridade mais alta à utilização do gás para criar uma indústria nacional e empregos, mesmo que reduza as receitas a curto prazo
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; rural development / desenvolvimento rural

Gas for development or just for money? - Hanlon, Joseph; Nuvunga, Adriano (Centro de Integridade Pública (Public Integrity Centre), 2015)
Mozambique’s gas can be used to promote industrialisation and rural development, but only if key choices are made now. Current priorities are for export based mega-projects promising high revenues, but like past mega-projects doing little to create jobs or reduce poverty. Mega-projects costing tens of billions of dollars are essential, but the Council of Ministers can instruct that negotiations give a higher priority to using the gas to create a domestic industry and jobs, even if it reduces short term income.
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; rural development / desenvolvimento rural

Natural Gas and Socio-Economic Transformation in Mozambique: Some Preliminary Evidence - Uetela, Pedro; Obeng-Odoom, Franklin (The Journal of Energy and Development, 2015)
The aim of this article is to extend the state of analysis on the impacts of gas development in Mozambique by evaluating the relationship between the gas sector, the Mozambican economy, and social change. As the resource curse framework is only limited to economic growth, this work utilizes two alternative frameworks—the Staples approach and the Linkages approach—that are melded into an institutional analysis, looking simultaneously at “benefits, costs, and uncertainties” or “blessings, uncertainties, and curses,” and used to conceptualize progress more widely to include not only growth, but other externalities and broader social change as applied to the case of Mozambique. In so doing, the evidence suggests that the natural gas industry in Mozambique has contributed to both the expansion in economic growth and social change. However, the positive experience with social change arises from direct intervention and not necessarily the result of the related economic growth. Indeed, in the process of economic growth, the production and export of natural gas in Mozambique have raised the possibility of major socio-economic and ecological dangers. Contrary to the theoretical criticism of spending windfall revenues on social services as wasteful, we argue that only strategic social and ecological expenditures of gas revenues can provide and increase the chances of the gas industry becoming transformational economically, socially, and ecologically. The article is organized as follows; the next section deals with conceptualizing the paper and describing the sources of data. This is followed by sections that present the results, a discussion of those results, and conclusions and policy implications from the study.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; ⛔ No DOI found

Indústria extractiva e desenvolvimento local: O papel da responsabilidade social empresarial - Langa, Epifânia; Massingue, Nelsa (Desafios para Moçambique, 2014)
A entrada de grandes investimentos de capitais estrangeiros na área de recursos minerais e energia, nos últimos anos, tem levantado várias questões sobre o papel dos mega ‑projectos no desenvolvimento económico e social em Moçambique, gerando um debate sem consenso. Uma das temáticas do debate é a responsabilidade social empresarial (RSE). Acções de RSE como a construção de infra ‑estruturas sociais para a educação e a saúde, a geração de emprego, entre outras são muitas vezes referenciadas em muitos discursos, principalmente políticos e de empresas, como aspectos positivos que complementam as acções do governo, devendo por isso ser promovidas e valorizadas.1 Entretanto, estes discursos muitas vezes negligenciam componentes não menos importantes como a intenção das empresas ao desen‑ volver iniciativas sociais, o risco das comunidades se tornarem dependentes destes mega ‑projectos e a possibilidade de fragilização do papel do Estado (Schroeder & Schroeder, 2004).
Keywords: G - Mozambique / Moçambique; L - portuguese / português; extractive industries / indústrias extractivas; natural resources / recursos naturais; private sector - CSR (corporate social responsibility) / setor privado - RSC (responsabilidade social corporativa); private sector / setor privado

Mozambique land policy development case study - Locke, Anna (Overseas Development Institute, 2014)
This case study has been produced in response to a request made to the Evidence on Demand Helpdesk. The objective of the request was to provide a detailed case study on the evolution of land policy in Mozambique and provide the reader with insights into what is viewed as one of Africa’s most progressive land laws, recognising multiple forms of tenure. Mozambique has experienced accelerated rates of growth over the past decade, averaging 7.2% per year, with projected growth rates of over 8%. However, this high growth rate has failed to translate into significant reductions in poverty and inequality has increased in almost all parts of the country. While growth has been driven by capital-intensive projects, mainly in the extractives sector, agriculture is seen as an important foundation for economic development and there has been a high level of interest in acquiring large tracts of land for investment over the past six years. Mozambique is one the most land-abundant countries in Africa, with around 80 million hectares (has). Currently, only five million hectares are cultivated, mainly by smallholders under rain-fed, traditional systems, and only 3-5% of landholdings are formally registered.
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; extractive industries / indústrias extractivas; governance / governação; land governance / gestão de terra

Mozambique’s Coming Natural Resource Boom Expectations, Vulnerabilities, and Policies for Successful Management - Biggs, Tyler (USAID, 2012)
Mozambique is set to become a world-class natural resource exporter with projections indicating that it will experience rapid increases in windfall revenues over the next several decades and well beyond. While this is welcome news for a low-income country with a substantial proportion of the population below the poverty line, it foreshadows some economic management problems ahead. The main concern is the poor economic record of many other lowincome countries with large natural resource endowments. It is remarkable how often these countries have experienced inferior rates of growth compared with countries lacking such endowments. This pattern, known as the ―natural resource curse,‖ has been documented in empirical research across a wide sample of nations.
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - english / inglês; extractive industries / indústrias extractivas; natural disasters / desastres naturais

Exploring Natural Resources in Mozambique: Will it be a Blessing or a Curse? - Bacuane, Aurélio; Mulder, Peter (Instituto de Estudos Sociais e Económicos (IESE), 2007)
Mozambique has considerable quantity of natural resources, of which the major part is yet to be explored. The Government of Mozambique is determined to extract and export its natural resource potential as soon as possible, supposing that this will positively contribute to economic growth and poverty reduction. However, any resources rich countries are among the poorest nations in the world, in spite of decennia-long exploration of their natural wealth. This so colled 'paradox of plenty' or 'resource curse' raises the question whether the foreseen exploration of natural resources in Mozambique will pose a serious threat rather than a blessing to its economic development. In this paper we first estimate the potential resource wealth of Mozambique in comparison to other countries. Next, we briefly review the rowing body of literature on the existence and determinants of a natural resource curse. Then we evaluate the risk of a resource curse to occur in Mozambique in the (near) future. Finally, we try to come up with suggestions to avert a Mozambican resource curse.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); extractive industries / indústrias extractivas; institutions / instituições; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; transparency / transparência

Mozambique LNG Project, Cabo Delgado, Mozambique
The Area 1 Mozambique LNG project comprises the offshore Golfinho-Atum gas field development and a 12.88Mtpa onshore LNG facility in Mozambique.
Keywords: FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; extractive industries / indústrias extractivas